Cinema and Philosophical Education: from Wittgenstein to Deleuze (European Journal of Language and Literature, 2015)
Bruce Russell argues, that cinema cannot create the philosophical knowledge for the reason that the answers to philosophical questions are contradictory and not obvious, the explicit argumentation is needed if the person is inclined to give justified answers to philosophical questions. Given examples are not satisfactory for philosophizing. On the other hand Slavoj Žižek, Stanley Cavell and Gilles Deleuze seems do not see this obvious gap between cinema and philosophy. They discuss the cinema as philosophy. What presumptions are needed for this approach? How this approach could be adapted in the philosophy education?